2006
DOI: 10.1177/1534765606297820
|View full text |Cite
|
Sign up to set email alerts
|

Multiple terrorist attacks: Compassion fatigue in Israeli social workers.

Abstract: With each recurrent terror attack in Israel, hospital social workers attend family members of the injured and the dead from the very first hours after the incident, giving them psychological first aid and information. The aims of the study were to assess the occurrence and levels of compassion fatigue and its correlates among hospital social workers. Fifty-three social workers from two major hospitals in Israel filled out the Secondary Traumatization and Burnout subscales of the Compassion Fatigue Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Eidelson et al (2003) reported that following 9/11, psychologists described feelings of loss, fear, pain and grief. Similar feelings of distress were related by Israeli social workers during times of terror (Cohen et al, 2006)-feelings that included pain, sorrow, fear, threat, uncertainty and sometimes even helplessness. Similar emotional distress was also reported by Shamai and Ron (2009).…”
Section: Negative Consequencesmentioning
confidence: 62%
See 2 more Smart Citations
“…Eidelson et al (2003) reported that following 9/11, psychologists described feelings of loss, fear, pain and grief. Similar feelings of distress were related by Israeli social workers during times of terror (Cohen et al, 2006)-feelings that included pain, sorrow, fear, threat, uncertainty and sometimes even helplessness. Similar emotional distress was also reported by Shamai and Ron (2009).…”
Section: Negative Consequencesmentioning
confidence: 62%
“…Most of the helping professionals after 9/11 reported feelings of helplessness due to the challenges posed by the large numbers of people trying to cope with intense pain (Eidelson et al, 2003). Helplessness has also been mentioned by professionals working with victims of terror in Israel, due to their limited ability to help their clients cope with the magnitude of their suffering (Cohen et al, 2006;Lev-Wiesel et al, 2008). Some professionals also report feelings of helplessness due to their sense of being in physical danger while lacking any means of protecting themselves (Shamai, 2005).…”
Section: Large-scale Traumatic Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that similar traumatic events were experienced in their previous experiences or professionally encountered incidents. Cohen, Gagin, and Peled-Avram (2006) reported in their study that 48.2% of social workers had a high rate of secondary traumatic stress symptoms. In this case, traumatic events can be claimed to trigger secondary traumatic stress symptoms, which leads to another social trauma (Maercker & Herrle, 2003) and difficult to prevent stresses.…”
Section: Discussionmentioning
confidence: 94%
“…The emergency phase, which necessitates changes in the mental health professionals' roles and obligations (Dekel and Baum, 2010;Tosone et al, 2003) as well as the physical settings in which their work takes place, also requires an immediate implementation of flexibility and creativity on the workers' part. For some, the abrupt changes in the settings and roles are distressing (Lev-Wiesel et al, 2009) and they may report high levels of helplessness attributable to the scope of the disaster (Eidelson et al, 2003), the pain and suffering endured by the victims (Cohen et al, 2006) and the social workers' own sense of exposure to danger while in the midst of offering mental health assistance (Shamai, 2005).…”
Section: Introductionmentioning
confidence: 99%